Factors associated with successful completion of the Chronic Disease Self-Management Program (CDSMP) among middle-aged and older Asian American participants: A national study - SangNam eAhn; SangNam eAhn; Matthew Lee Smith; Matthew Lee Smith; Jinmyoung eCho; Luohua eJiang; Lindsey ePost; Marcia eOry (Frontiers Media S.A., 2015)
.